2022
DOI: 10.7861/clinmed.2021-0512
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a virtual ward delivering oxygen at home for patients recovering from COVID-19: a real world observational study

Abstract: BackgroundThere is a lack of data on the safety of providing oxygen at home to stable patients recovering from COVID-19. Methods A retrospective analysis of patients discharged to a COVID-19 virtual ward (CVW) between January 2021 and March 2021 at a UK district general hospital was performed. Patients with improving clinical trajectories and oxygen requirements up to 4 L/minute were eligible. Outcomes measured were 30-day mortality and readmission rate. ResultsFrom 02 January 2021 to 16 March 2021 (74 days), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Studies report high satisfaction rates for monitoring in their own home environment [ 12 14 , 15 ▪ , 16 ]. One study compared home monitoring combined with and without oxygen (up to 4 l/min) and found comparable readmission rates and mortality, which supports the safety of oxygen at home [ 17 ]. In conclusion, early discharge with home monitoring, oxygen and medication is safe.…”
Section: Hospital Care At Home: Virtual Wardmentioning
confidence: 93%
“…Studies report high satisfaction rates for monitoring in their own home environment [ 12 14 , 15 ▪ , 16 ]. One study compared home monitoring combined with and without oxygen (up to 4 l/min) and found comparable readmission rates and mortality, which supports the safety of oxygen at home [ 17 ]. In conclusion, early discharge with home monitoring, oxygen and medication is safe.…”
Section: Hospital Care At Home: Virtual Wardmentioning
confidence: 93%
“…Previous studies have focused on the development of virtual wards for specific conditions or groups of patients. For the UK, one of the first countries to trial virtual wards, literature is scarce and the size of virtual wards is smaller compared with the one presented here 3 13 14. In addition, this study is the first example of the assessment of virtual ward cost-effectiveness in the UK within a medium-size hospital facility.…”
Section: Discussionmentioning
confidence: 93%
“…Supplemental oxygen therapy has been described as part of relatively few remote monitoring pathways, used either to prevent the need for admission to hospital or to facilitate early supported discharge from hospital [ 16 , 30 32 ]. Some pathways were designed solely for those requiring home oxygen therapy, whereas others offered home oxygen therapy as part of a wider oximetry monitoring programme.…”
Section: Purpose and Scope Of Home Oxygen Monitoring And Therapy Prog...mentioning
confidence: 99%
“…No deaths occurred in the ambulatory setting, however, the absence of a control group in this study means findings should be interpreted with caution [ 31 ]. A similar study from the United Kingdom of patients with COVID-19 monitored at home with pulse oximetry found no significant difference in the odds of admission or mortality within 30 days of discharge from hospital between those receiving and those not receiving home oxygen [ 32 ]. A study from the Netherlands of 196 patients receiving early supported hospital discharge onto a home oxygen programme for the treatment of COVID-9 was associated with a reduction in length of hospital stay of 6.4 days [ 30 ].…”
Section: Evidence For the Effectiveness Of Oxygen Therapymentioning
confidence: 99%